BASKETBALL DEFENSE: A TECHNICAL, TACTICAL, AND TEACHING - LEARNING APPROACH (Fiep Bulletin - online, 2013)
Defense training in basketball involves aspects that must be observed during a player's career. Similarly to the way offense can be learned, through practice of technical gestures and validated forms of teaching, it is also possible to learn how to defend in basketball. The individual and zone defense are the main used in this sport. The defense techniques can be taught to the athletes from the initiation, taking into consideration the limitations imposed by age and ability level. It is notable that the defense techniques also play a crucial role in the learning of basketball. To become a great athlete, consistent defensive and offensive abilities are necessary. Tactically, the athlete must be able to make correct decisions during a match, given the short time for decision making. The teaching-learning of the defense in basketball should follow pedagogic principles that allow the development, for each age group, of the technical and tactic capacities. The teaching of the defensive bases through the situational method and reduced games can be an alternative for the initiation.
Keywords: Basketball; defense basketball; teaching-learning